Antitumor effect of a short peptide on p53-null SKOV3 ovarian cancer cells. Issue 10 (November 2019) - Huang, Yi-shan; Wang, Tian-xiang; Lin, Xiao-mian; Wang, Heng; Li, Rong-zhen; Zeng, Xiangfeng; Zhu, Cairong; Chen, Lian-kuai; Guo, Qiuxiao; Liu, Hongjiao; Wu, Xiao-ping
Abstract : Fibroblast growth factor-2 (FGF2) is a protein ligand, which exerts essential roles in development, angiogenesis, and tumor progression via activation of the downstream signaling cascades. Accumulating evidence has demonstrated that FGF2 is involved in the progression of ovarian cancer, providing a novel potential target for ovarian cancer therapy. In this study, we showed that FGF2 is significantly increased in ovarian tumors, and is negatively associated with the overall survival of ovarian cancer by database analysis. A short peptide obtained from a heptapeptide phage display library suppressed FGF2-induced proliferation, migration, and invasion of the p53-null epithelial ovarian cancer (EOC) cells. Further investigations revealed that the short peptide antagonized the effects of FGF2 on G0/G1 to S cell phase promotion, cyclin D1 expression, and MAPK and Akt signaling activation, which might contribute to the mechanism underlying the inhibitory effects of the short peptide on the aggressive phenotype of the ovarian cancer cells triggered by FGF2. Moreover, the short peptide might have the potentials of reversing FGF2-induced resistance to the doxorubicin via downregulation of the antiapoptotic proteins and counteracting of the antiapoptotic effects of FGF2 on p53-null EOC cells. Taken together, the short peptide targeting FGF2 may provide a novel strategy for improving the therapeutic efficiency in a subset of EOC.